100-m-resolution surface soil moisture data during the thawing season on the Qinghai‒Tibet Plateau - Zhibin Li; Lin Zhao; Lingxiao Wang; Guangyue Liu; Erji Du; Defu Zou; Guojie Hu; Zanpin Xing; Chong Wang; Shibo Liu; Minxuan Xiao; Luhui Yin; et al. (Scientific Data)
Abstract The characteristics of the spatial distribution of surface soil moisture (SM) on the Qinghai‒Tibet Plateau (QTP) on a fine scale are unclear due to the lack of high-spatial-resolution SM datasets. To improve this situation, we first supplemented 659 SM datasets in areas on the QTP containing sparse monitoring stations from 2021–2022 and integrated published SM datasets. Based on Sentinel-1&2 and measured SM data, we developed an SM retrieval algorithm for the ascending and descending orbits. Then, 100-m-resolution SM spatial data were generated for the thawing season of 2017–2023 in the SAR signal-applicable area on the QTP. As validated by the measured data, the correlation coefficients of the retrieval results for the ascending and descending orbits were 0.72 and 0.69, respectively, and the bias reached 0.07 m³/m³ and an RMSE of 0.07 m³/m³ for both. These SM datasets exhibit notable promise for improving our understanding and analysis of the ecology and hydrology of different environments on the QTP.